(untitled) (Annals of Medical Research, 2021)
Aim: Transforaminal epidural steroid injection reduces the low back-leg pain which caused by lumbar disc herniation (LDH). The aim of our study is to evaluate the treatment of transforaminal epidural steroid injection for recurrent LDH. Materials and Methods: 19 patients were included in our study who were treated by transforaminal epidural steroid injection for recurrent LDH in our clinic between 2014 and 2018. We evaluated the patients pre-procedure and at 2 weeks, 3 and 6 months after treatment by Visual Analogue Scale / Oswestry Disability Index (ODI) and followed up for surgical treatment after 6 months.Results: The mean low back and leg pain VAS was 4.2±0.6 before TFESI procedure and it was 1.9±0.3 after two weeks. İt was 2.1±0.3, 3.6±0.8 at 3 and 6 months after procedure respectively. The reduction of low back and leg pain mean VAS is statistically significant between before treatment and at 2 weeks and at 3 months after TFESI procedure respectively (p0.05). The mean ODI was 21.4±0.3 before TFESI procedure and it was 12.4±0.7 after two weeks. İt was 15.3±0.5 and 18.2±0.1 at 3 and 6 months after procedure respectively. The four of all patients were treated by microdiscectomy for recurrent LDH.Conclusion: The transforaminal epidural steroid injection is safely treatment for non-surgical treatment of recurrent LDH. Our study recommends that transforaminal epidural steroid injection should be considered before surgical intervention and this procedure may support to surgical indication of recurrent LDH.